(Design and Performance Testing of Dryer and Clarifyer Equipment on Processing of Virgin Coconut Oil) - H Guring Pohan; Dadang Supriatna (Balai Besar Industri Agro, 2004)
Design and performance testing study of the dryer and the clarifyer equipments of Virgin Coconut Oil (VCO) has been done for producing better quality of the product. The power of the electrical motor for stirrer of the dryer used was 5 hp and it has reduced from 1500 rpm to 300 rpm using gear box T.S. 80 type and finally become 4 rpm on the stirrer in order to running well. Electrical motor connected to the timer apparatus to change the rotation of the dryer which automatically work well so that the grated coconut meat to be dried accepted the heat energy uniformly. The flow direction of the refinery of oil and the fluid (mix of the oil and water) from the bottom of the refine equipment was raised up and then went down to the bottom, so that the oil product did not break to the treatment of heat. According to this indicated that the stirrer apparatus could worked well. Analytical result shows that the VCO moisture content is 0,11 %, free fatty acid is 0,22 % and lauric acid is 49,92 %. The whole of equipments system process is running well. Drying rate of water at 70 C, condition is 7,9% (w/w) per hour, heating efficiency is 18,99% at 6 hours drying time, capacity of dryer 231,1 kg per batch, efficiency of the refinery oil per batch 97 %.